6+(y+5)=(6+y)+5

Simple and best practice solution for 6+(y+5)=(6+y)+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+(y+5)=(6+y)+5 equation:


Simplifying
6 + (y + 5) = (6 + y) + 5

Reorder the terms:
6 + (5 + y) = (6 + y) + 5

Remove parenthesis around (5 + y)
6 + 5 + y = (6 + y) + 5

Combine like terms: 6 + 5 = 11
11 + y = (6 + y) + 5

Remove parenthesis around (6 + y)
11 + y = 6 + y + 5

Reorder the terms:
11 + y = 6 + 5 + y

Combine like terms: 6 + 5 = 11
11 + y = 11 + y

Add '-11' to each side of the equation.
11 + -11 + y = 11 + -11 + y

Combine like terms: 11 + -11 = 0
0 + y = 11 + -11 + y
y = 11 + -11 + y

Combine like terms: 11 + -11 = 0
y = 0 + y
y = y

Add '-1y' to each side of the equation.
y + -1y = y + -1y

Combine like terms: y + -1y = 0
0 = y + -1y

Combine like terms: y + -1y = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 13x-(5x-4)=20 | | 3k-8/4=5 | | 56633+555x=89 | | 7x+5=3x-6 | | 2(x+6)/3=3x-3 | | 9a+48=6a+50 | | 3(a-4)-2(a-5)=4a+6 | | -5(-7-3x)=125 | | 7+3x/2=5x/3 | | 145-4x=41x+20 | | 3x-4=4-x | | -3/2x-4/3y=16 | | 8-7x-6x=-5x+16 | | 2x+6+3(x-8)=3(-8+x) | | 0.25(16x+6)-3x+5=2-2x | | (m/8)+3=16 | | 9/10-3/4 | | -26r=34 | | 9-7x=73+21x | | 2.7x+1.1=6.5 | | 5/2x-8=x+4+3/2x | | 0.5x-0.3=1.2 | | 7/8m=49 | | 3-7m=17 | | 0.2x+6=16 | | 5x-4=2x-16 | | p+(-54)=27 | | -2p=-10 | | n-(-5.6)=-0.34 | | 0.25x-0.2=1.3 | | -1-3n=3n+5 | | 0.15*52= |

Equations solver categories